Tracheostomy stomal seeding following oral cavity resection. (April 2021) - Hintze, J.M.; Fitzgerald, C.; Lang, B.; O'Shea, J.; Barry, C.; Brennan, S.; Lennon, P.
Abstract: Background: Tracheal stoma recurrence following oral cavity surgery is exceedingly rare. Although several different mechanisms for this have been described, the pathogenesis still remains uncertain. Methods: We present the case of a gentleman who presented 6-months following oral cavity SCC resection with a large fungating mass at his previous tracheostomy site, and also review the reported literature on this rare phenomenon. Results: Four weeks after diagnosis of his recurrence he underwent a total laryngectomy, wide-local skin excision and reconstruction with a pectoralis major pedicled flap. He recovered well initially following his operation, however unfortunately contracted nosocomial SARS-Cov2 and succumbed from respiratory complications during his post-operative recovery. Conclusion: Stomal recurrence after temporary tracheostomy for oral cavity malignancies are very rare. Previously reported management of these can vary from surgical to palliative treatment. Methods to prevent these include delaying tracheostomy until after surgical resection, packing the pharynx during resection and adjuvant radiotherapy.